Patient-oriented educational Sports Medicine YouTube videos in Arabic have higher view counts in the Middle East and North Africa than their English versions - Theodorakys Marín Fermín (12199534) (2023)
Purpose The present study aims to assess the impact of the local language on the view count of patient-oriented educational Sports Medicine videos in an Orthopaedic and Sports Medicine Hospital in the Middle East and North Africa. Methods An observational study on English and Arabic versions of Aspetar’s YouTube channel patient-oriented educational video series was conducted in February 2023, comparing the view count and viewer characteristics. Included videos were posted either simultaneously or in English version first, in both languages, and shared on the same media platforms. Collected data of interest included video title, view count in each language, age and sex of the viewers, location, and traffic source. Results Eleven videos of the patient-oriented educational video series were included in the present study. Except for one, the view count was significantly higher in the Arabic version of all 11 videos (minimum sevenfold, P = 0.03). Viewers were predominantly males (73.9%) and between 18 and 44 years old (81.1%). Eleven out of 19 countries of the Middle East and North Africa region [11] were among the viewers’ top 20 countries. Traffic sources included YouTube search (45.9%), YouTube suggested videos (17%), external sources (14.4%), YouTube browse features (8.5%), and YouTube advertising (6%). Conclusion Patient-oriented educational Sports Medicine videos in Arabic yield higher view counts than their English version in young adult viewers from 11 countries in the Middle East and Africa among the top 20. Content creation on languages with limited online representation could effectively reach the targeted population by breaking language barriers. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00264-023-05970-z Additional institutions affiliated with: Surgical Specialty Center - Hamad General Hospital